ANALISIS KEBIJAKAN PENDIDIKAN MENENGAH DI INDONESIA TANTANGAN, IMPLEMENTASI, DAN ARAH PENGEMBANGAN - Dahliah; Nurhidayah; Bagus Pujianto; La Ridwan; Syumardi; Norma; Sirajuddin Saleh (STKIP Subang, 2026)
Secondary education plays a strategic role in the development of human resources in Indonesia. This article aims to analyze secondary education policies in Indonesia, covering the regulatory framework, policy implementation, challenges encountered, and future development directions. This study employs a qualitative approach using a literature review method, drawing on regulations, scholarly articles, as well as reports from national and international institutions. The findings indicate that since the enactment of Law Number 20 of 2003 concerning the National Education System, there have been significant policy developments. However, policy implementation continues to face various challenges, including disparities in educational quality across regions, limited infrastructure, unequal distribution of teaching personnel, and a mismatch between curriculum and labor market demands. The main findings reveal that the core issues in secondary education policy lie not only in regulatory aspects but also in disparities in implementation across regions, institutional capacity, and the readiness of human resources in the education sector. Therefore, future policy development should focus on expanding equitable access, improving the quality of learning, strengthening governance, and integrating digital technology into education. This article contributes by providing a critical synthesis of secondary education policies as a basis for formulating more adaptive and sustainable policy directions.